Oculoplastic Surgeries in Patients Older than 90 Years of Age. Issue 4 (July 2022) - Abumanhal, Muhammad; Feldman, Ilan; Leibovitch, Igal; Cnaan, Ran Ben
Purpose: To report the epidemiology, indications and surgical outcomes of oculoplastic surgeries in older adults (≥ 90 years old). Methods: A retrospective study was conducted reviewing the medical charts of 114 patients aged 90 years old and older who underwent oculoplastic procedures from 2010 to 2020. Data retrieved from the medical records included: past medical and ocular history, indication for surgery, type of surgery, intra and post-operative complications, pathological analysis for removed tissues, and surgical outcome in the last follow-up. Results: One hundred and twenty eight surgeries were performed on 114 patients (male: female = 1:1). The mean age was 92.95 years old (± 3.12 SD). Six patients (5.2%) were older than 100 years old. The most common indication for surgery was lower lid malpositioning (32%). Mass/lesion excision was performed in 34 procedures (25%). Forty-three biopsies were analyzed and basal cell carcinoma was found to be the most common pathological diagnosis (32%). Hypertension was the most common associated systemic comorbidity (79 patients, 69%). 80% of the surgeries were performed under local anesthesia. Surgical revision was required in seven patients (5.2%). One patient had suffered from a minor stroke one day after the surgical pocedure. The same patient had orbital-skin fistulas after orbital exenteration Conclusion: In our experience, oculoplastic surgeries among the elderly population are safe without significant complications and can usually be performed under local anesthesia. Advanced age should not prevent surgery, especially if the procedure may improve vision and quality of life.